(untitled) (Law Research Review Quarterly, 2026)
The Food Estate Program is one of the government’s strategic policies in an effort to strengthen national food security, including at the village level. In its implementation, Village-Owned Enterprises (BUMDes) have the potential to play a role as implementers of village economic activities that support the strengthening of local food systems. This study aims to analyze the legal construction of the position of BUMDes as the implementer of the village-scale Food Estate program and to examine the role of BUMDes in realizing local food security and legal protection for farmers. This study uses a normative legal research method with a legislative and conceptual approach. The results of the study show that BUMDes has a strong legal basis for involvement in the management of business activities related to the food sector as regulated in Government Regulation Number 11 of 2021 concerning Village-Owned Enterprises. In practice, BUMDes can play a role in strengthening the village food value chain through production, processing of agricultural products, and distribution and marketing of agricultural products. However, the implementation of this role still faces various obstacles related to legal substance, institutional structure, and the legal culture of the community. Therefore, strengthening the BUMDes institution and providing legal protection for farmers through clear and fair cooperation agreements are important factors in supporting the success of the village-scale Food Estate program.